Recreational cultural ecosystem services: How do people describe the value? - Stålhammar, Sanna; Pedersen, Eja (Ecosystem services, 2017)
•It is important to know if the CES framework is coherent with people’s view of values of their recreational experiences.•We used an interpretivist approach using focus group material in Southern Sweden.•Value was described as axiomatic, i.e. indivisible and incommensurable.•Benefits were perceived through naturalness and experiences of authenticity, healing, beauty, magic, and movement.•Preference-based valuation could be in conflict with the individuals’ way to reflect on nature values. Different ways of viewing human-nature interactions affect the ways in which these are conceptualized and operationalized with regards to cultural ecosystem services (CES). To clarify if some conceptualizations provide more appropriate descriptions of benefits, these need to be discussed in relation to the lived experience. This paper addresses some aspects of the controversy around the use of the concept of CES and associated framing of ‘values’. Our aim is to understand potential distinctions between individuals’ expressions of values of their experiences and the language of value of ES. We use Swedish focus group material formed to understand how individuals perceive and express their values of the experiences of spending time in natural environments in their own words. We apply an interpretivist approach inspired by grounded theory and present our findings as the broader interpretative repertoire ‘axiomatic value’. The interpretative repertoire informed three discourses that participants describe as valuable in relation to experiences in nature: ‘indivisibility’, ‘incommensurability’, and ‘the goodness of perceived naturalness’. The latter comprised the underlying themes ‘nature as authentic’, ‘nature as healing’ and ‘nature as beauty, magic and movement’. We discuss implications for conceptualizations of value and question the appropriateness of the non-contextual and categorical language of ES.